PENDAMPINGAN IMPLEMENTASI MEDIA ETHNO WEB DIGITAL DI SEKOLAH INKLUSI - Zayyadi, Moh; Lanya, Harfin; Linarsih, Yanti; Mosdalifah, Mosdalifah; Saputra, Andi (UNIVERSITAS PGRI MADIUN, 2024)
Abstract. The aim of the dedication is to help in the implementation of digital ethno web media at the Gladak Anyar 2 Pamekasan elementary school. Gladak Anyar 2 State Elementary School is one of the inclusive schools in Pamekasan Regency. Ethno web digital learning media provides space for teachers to adjust the learning materials that will be given to students. The method of implementing this activity is problem identification, creating digital ethno web media, mentoring, and evaluation. Partner schools have digital ethno-web learning media that can be used in implementing the independent curriculum, differentiated learning, and strengthening the profile of Pancasila students. Implementation of the use of digital ethno-web for students with special needs which can improve learning outcomes. digital ethno-web-based applications can help in developing skills in using technology in learning.Abstrak. Tujuan pengabadian adalah melakukan pendampingan implementasi media ethno web digital di sekolah dasar Gladak Anyar 2 Pamekasan. Sekolah Dasar Negeri Gladak Anyar 2 merupakan salah satu sekolah inklusi yang ada di Kabupaten pamekasan. Media pembelajaran ethno web digital memberikan ruang bagi guru untuk menyesuaikan materi pembelajaran yang akan diberikan ke siswa. Metode pelaksanaan dari kegiatan ini adalah identifikasi masalah, pembuatan media ethno web digital, pendampingan, dan evaluasi. sekolah mitra memiliki media pembelajaran ethno-web digital yang dapat digunakan dalam implementasi kurikulum merdeka, pembelajaran berdiferensiasi dan penguatan profil pelajar pancasila. Implementasi penggunaan ethno-web digital bagi siswa berkebutuhan khusus yang dapat meningkatkan hasil belajar. aplikasi berbasis ethno-web digital dapat membantu dalam pengembangan keterampilan pemanfaatan teknologi dalam pembelajaran.